2004
DOI: 10.1111/j.1479-828x.2004.00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for colposcopy in the follow‐up of treated low grade squamous intraepithelial lesions?

Abstract: Is routine colposcopy justified in the follow up of treated low grade squamous intraepithelial lesions (LGSIL) of the cervix? This retrospective study analysed the notes of women treated at a public hospital colposcopy clinic over a 5-year period. Two hundred and fifty women fulfilled the inclusion criteria of whom 11 had persistent disease. Of these, only one case of LGSIL was detected by colposcopy in the absence of abnormal cytology. In the present study, routine colposcopy offered minimal additional benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Success rate after initial treatment was determined to be 95.6%. [3] In the present study, persistent disease was found in 38 of 240 patients, and progression was seen in 16.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Success rate after initial treatment was determined to be 95.6%. [3] In the present study, persistent disease was found in 38 of 240 patients, and progression was seen in 16.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies have shown that using merely colposcopy on follow-up has low sensitivity. [3] It has been shown that 70% of LSIL lesions regress on their own; however, 10% progress to HSIL. [11,12] Petry et al reported 30.2% CIN 3 and 1% cervical carcinoma in LSIL patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation